2018
DOI: 10.1109/tmtt.2017.2786729
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Nonlinear RF Cancellation for Improved Isolation in Simultaneous Transmit–Receive Systems

Abstract: This paper proposes an active radio frequency (RF) cancellation solution to suppress the transmitter (TX) passband leakage signal in radio transceivers supporting simultaneous transmission and reception. The proposed technique is based on creating an opposite-phase baseband equivalent replica of the TX leakage signal in the transceiver digital front-end through adaptive nonlinear filtering of the known transmit data, to facilitate highly accurate cancellation under a nonlinear power amplifier (PA). The active … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 36 publications
0
46
0
Order By: Relevance
“…transmits and receives simultaneously, there will be self-interference (SI) swamping the signal received from the source node. However, the experimental results in [2]- [6], [13]- [15] have demonstrated that SI signal can be efficiently suppressed. Hence, the residual self-interference (RSI) should be included in the description of the received signal at the relay, which is given as…”
Section: System Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…transmits and receives simultaneously, there will be self-interference (SI) swamping the signal received from the source node. However, the experimental results in [2]- [6], [13]- [15] have demonstrated that SI signal can be efficiently suppressed. Hence, the residual self-interference (RSI) should be included in the description of the received signal at the relay, which is given as…”
Section: System Modelmentioning
confidence: 97%
“…Moreover, a hybrid SIC system, which comprises adaptive radio frequency (RF) cancellation and digital cancellation schemes, was proposed in [5]. Next, an active RF cancellation algorithm that exploits adaptive nonlinear filtering to attain effective SI cancellation when a nonlinear power amplifier (PA) is used, was presented in [6].…”
Section: Introductionmentioning
confidence: 99%
“…Using β = 1 implies that the residual interference increases linearly with the relay transmit power P r and the chosen value of α corresponds to a 40dB interference cancellation. This can be achieved through a common passive device, like a circulator, which is able to provide 20-40 dB isolation between the transmit and receive chains [28] [46]. We see that for low source transmit powers, the active cancellation FD is unable to harvest sufficient power for cancellation and transmission, and therefore achieves zero rate for P s ≤ 20 dBm.…”
Section: A Algorithm Convergence and Complexitymentioning
confidence: 99%
“…e reconstruction may also be done equivalently in the digital domain, where the digital baseband signal is ltered and then converted to the RF signal by an auxiliary transmit chain. Kiayani et al [11] report that their MRP scheme of this form cancels up to 54 dB for 20 MHz bandwidth. ese two kinds of RF-SIC schemes, as shown in experimental results of previous studies, have reduced self-interference signi cantly; however, their theoretical cancellation capability has not been presented yet.…”
Section: Introductionmentioning
confidence: 99%
“…erefore, there is a fundamental issue, i.e., selfinterference cancellation, in full-duplex wireless communication. Recent studies have shown that a strong selfinterference should be cancelled first in the RF domain to ensure the useful signal to pass through RF front end [3][4][5][6][7][8][9][10][11][12][13][14]. e commonly used RF-SIC schemes may be divided into two kinds.…”
Section: Introductionmentioning
confidence: 99%